Bimodal response to aspirin loading in acute ST-elevation myocardial infarction. (September 2013) - Fefer, Paul; Beigel, Roy; Varon, David; Shenkman, Boris; Shechter, Michael; Savion, Naphthali; Hod, Hanoch; Matetzky, Shlomi
<x xml:space="preserve">Abstract</x> Patients with stable coronary disease who exhibit platelet hypo-responsiveness to aspirin (ASA) have worse outcomes. Little data exist regarding platelet response to ASA in ST-elevation myocardial infarction (STEMI) patients. Our objective was to assess acute platelet response to ASA loading in STEMI patients undergoing primary percutaneous coronary intervention (PCI). The study comprised 102 consecutive patients with STEMI. All patients received a loading dose of 300 mg chewable ASA upon admission. Platelet reactivity was assessed immediately prior to primary PCI, at a median of 95(63 139) minutes after ASA loading. A bimodal response to arachidonic acid (AA) stimulation was observed, such that two distinct populations could be discerned: "good responders" had a mean AA-induced platelet aggregation of 36 ± 11% vs. 79 ± 9% for "poor responders." Despite equivalent demographic, clinical, and angiographic characteristics, good responders were significantly more likely to demonstrate early ST-segment resolution ≥70% after primary PCI (80% vs. 48%, p = 0.001), suggestive of better myocardial reperfusion. Early inhibition of AA-induced platelet aggregation post-ASA loading in the setting of STEMI is associated with better tissue reperfusion; however, a sizeable proportion of patients do not achieve significant inhibition of AA-induced platelet aggregation in response to ASA loading at the time of primary PCI.